تفسیر لغوی پر حضرت عبد اللہ ابن عباس رضی اللہ عنہما کے اسلوب ومنہج کے اثرات: The Impacts of Hazrat Abdullah ibn Abbas’s Exegetical Methodology and Style on Lexical Qur’anic Interpretation - Dr Hafiz Muhammad Ramzan; Mahboob-UR-Rahman (Al Manhal Research Journal, 2024)
The Holy Qur'an is such a light, whose lamp will never dim, and it is an ocean whose shore will never be found, and for the eternal religion, Allah has given the eternal book. The Holy Quran’s light will never lose their brightness, it is an unfathomable ocean. Allah has bestowed it an eternal book due to its eternal position among other religions. Literary interpretation of Holy Quran stands on the position as ancient knowledge of the Quranic sciences which started from revelation of Holy Prophet (peace be upon him). Its requirement originated with the revelation of the Qur'an. When the Companions of Prophet Muhammad (PBUH) faced difficulty in understanding of literal interpretation of Holy Quran they contacted to Holy Prophet for interpretation. The Prophet taught them the art of literal interpretation. The Prophet Muhammad advised them to have to understand the eloquent language of the Holy Qur'an, therefore you can understand the mysteries language of the Qur'an. Surely, Allah loves those who tried to understand the eloquent language of the Holy Qur'an. Keeping this importance in mind, the Companions of the Prophet and especially Hazrat Abdullah ibn Abbas emphasized on understanding the Arabic language to understand the literal interpretation and taught his students to adopt the same manner and style. To observe the important role of Hazrat Abdullah ibn Abbas in literal interpretation is the main reason for the selection of this topic. The present study will discuss the process of literal interpretation which the Prophet (ﷺ) taught to his Companions and to the Companions of the Tabieen, until this process became the book of Tafseer.